Coupling of Bi2O3 nanoparticles with g-C3N4 for enhanced photocatalytic degradation of methylene blue. Issue 4 (15th February 2021) - Fan, Guang; Ma, Zhanying; Li, Xiaobo; Deng, Lingjuan
Abstract: Tremendous demands for visible-light-induced catalysts with excellent degradation performance have attracted wide spread attention on designing versatile Bi2O3-based heterojunctions. Herein we designed and synthesized Z-scheme Bi2O3/g-C3N4 heterojunctions using in-situ thermal polymerization method. A tight contact interface between Bi2O3 and g-C3N4 confirmed the formation of heterojunction, facilitating the efficient separation of photo-generated charge carriers. In comparison with pure Bi2 O3 and g-C3 N4, the 0.5-Bi2 O3 /g-C3 N4 heterojunctions showed enhanced visible-light-induced catalytic activity which could degrade 100% of methylene blue within 90 min OH radicals played the most crucial roles and O2 −, h +, e − radicals were less contributing in methylene blue photocatalytic elimination. According to the direct evidence of active species capture experiment, PL spectra, HRTEM and well-matched band positions, a Z-scheme enhanced photocatalytic mechanism was put forward. In addition, possible degradation pathways for methylene blue were deduced according to the UPLC-MS results. The present research may provide a way for developing novel Bi2 O3 -based materials with special application in environmental purification.